VD_FINDINFO Jug / 2023 / 15 vom 17. Mai 2022 - VD Tribunal cantonal (2022)
LÉSION CORPORELLE GRAVE, TENTATIVEDROIT PÉNAL, LÉGITIME DÉFENSE, CONSTATATION DES FAITS, DÉTENTION ILLICITE | 15 CP, 16 CP, 22 ad 122 CP, 10 CPP (CH), 389 CPP (CH)